2017
DOI: 10.12669/pjms.333.12098
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of beta thalassemia trait from iron deficiency anemia by hematological indices

Abstract: Objective:We aimed at finding out reliable parameter in the differentiation of iron deficiency anemia (IDA) and beta-thalassemia trait (β-TT) in the adult population subjected to Saudi Arabian Premarital Screening Program.Methods:A total of 620 adults (age range 21-36 years) reported during February 2012 to November 2012. Tests for serum iron and ferritin were carried out in individuals showing low hemoglobin (Hb). All the selected subjects’ samples were subjected to blood morphology, comparison of MCV, RBC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 18 publications
2
43
0
Order By: Relevance
“…The RDWI had high YI (81.6%). These results are consistent with the findings of other relevant studies who found that the highest YI was obtained for RDWI 69.2%, 83% and 73.8% respectively[23] [24]…”
supporting
confidence: 93%
“…The RDWI had high YI (81.6%). These results are consistent with the findings of other relevant studies who found that the highest YI was obtained for RDWI 69.2%, 83% and 73.8% respectively[23] [24]…”
supporting
confidence: 93%
“…Another interesting finding was the tendency of red cell volume distribution width (RDW) elevation proportionally to the loss of the alpha genes, corroborating with other studies in the literature. e thalassemia patients have smaller and more homogeneous erythrocytes (mainly microcytic), which leads us to correlate high RDW in iron deficiency than in thalassemia [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…In India, on an average estimate 8000-1000 children are born every year with thalassemia major disease [10]. Several studies in the literature have reported that Sindhi community has high frequency of thalassemia along with similarity in clinical features of iron deficiency and traits of β thalassemia [7,11]. In the present study, traits of β thalasemia and iron deficiency anemia cases were confirmed by HbA2 levels and serum ferritin levels with the study of red cell indices MCV, MCH, RBC count and RDW.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology Update: Tropical Journal of Pathology & Microbiology Available online at: www.medresearch.in 450 | P a g e and reduce unnecessary cost [7][8][9]. Long term objective of this study was screening of anemic individuals of Sindhi community for thalassemia trait and to reduce the disease burden and preventing the inheritance by proper counseling and awareness also at lower cost and even in small set ups.…”
Section: Original Research Articlementioning
confidence: 99%